Through the Prevention Program for Eradication of Abuse and Illicit Trafficing of Drugs (P4GN) in Bandung City - Andi Sukandi (Decision, 2026)
This journal was prepared to investigate how the policy network participates in the program to prevent the eradication of drug abuse and illicit trafficking (P4GN) in Bandung. What is the Bandung City Government doing in collaboration with the Bandung City BNN to prevent drug misuse and illicit trafficking (P4GN) in Bandung City? Bandung City's P4GN prevention program aims to reduce drug usage and unlawful trafficking. The Prevention Program for the Eradication of Drug Abuse and Illicit Trafficking (P4GN) is an ongoing effort by various components of society and the government, both nationally and internationally, to raise community awareness about the dangers of narcotics, psychotropics, and other addictive substances. The Bandung City Government, specifically the Bandung City BNN, and the community play an important part in ensuring that this program prevents and eradicates drug trafficking in Bandung. This paper employs qualitative methods of descriptive analysis with secondary data collection from old books, journals, articles, and websites that focus on the role and involvement of actors in the sustainability of the prevention program to eradicate drug abuse and illegal trafficking. The purpose of this study is to determine the importance of actors in the long-term viability of a prevention program to eradicate drug abuse and illicit trafficking (P4GN).